Voriconazole: a review of adjustment programs guided by therapeutic drug monitoring - Jiang, Li; Lin, Zhiqiang (Frontiers in Pharmacology, 2024)
Objectives: Exploring adjustments to the voriconazole dosing program based on therapeutic drug monitoring results to implement individualized therapy. Methods: PubMed and Embase were systematically searched to obtain study about voriconazole dose adjustment program guided by therapeutic drug monitoring. Quality evaluation and summarization of the obtained studies were performed to obtain program adjustments for voriconazole under therapeutic drug monitoring. Results: A total of 1356 and 2979 studies were searched on PubMed and Embase, respectively, and after removing irrelevant and duplicated studies, a total of 25 studies were included. A loading dose of 5 mg/kg q12h or 200 mg q12h and a maintenance dose of 50 mg q12h or 100 mg q24h is recommended for patients with Child-Pugh C. And in patients with Child-Pugh C, CYP2C19 genotype had no significant effect on voriconazole blood concentrations. Recommendations for presenting dosing programs based on different CYP2C19 genotypes are inconsistent, and genetic testing is not routinely recommended prior to dosing from a pharmacoeconomic perspective. Additionally, in adult patients, if the voriconazole trough concentration is subtherapeutic, the voriconazole dose should be increased by 25%~50%. If the voriconazole trough concentration is supratherapeutic ,the voriconazole dose should be decreased by 25%~50%. If a drug-related adverse event occurs, hold 1 dose, decrease subsequent dose by 50%.In pediatric patients, if the voriconazole trough concentration is subtherapeutic, increase the voriconazole dose by 1~2 mg/kg or increase the voriconazole dose by 50%. If the voriconazole trough concentration is supratherapeutic, reduce the voriconazole dose by 1 mg/kg or hold 1 dose, and decrease the subsequent dose by 25%. Conclusions: It is recommended that all patients on voriconazole should have their initial dosing program selected on the basis of their hepatic function or other influencing factors (e.g., pathogens, infections, C-reactive protein, albumin, or obesity), and that therapeutic concentrations should be achieved through appropriate dosage adjustments guided by therapeutic drug monitoring. Routine genetic testing for voriconazole application in patients is not considered necessary at this time. However, there has been a great deal of research and partial consensus on individualized dosing of voriconazole, but there are still some critical issues that have not been resolved.